A case of brucellosis presenting with pericardial and pleural effusion. (14th March 2016) - Altas, Meryem Hilal; Karli, Arzu; Sensoy, Gulnar; Koken, Ozlem; Yurek, Burak; Baysal, Kemal
Abstract: Brucellosis is a worldwide zoonotic infection with a diverse clinical presentation. Pericardial and pleural involvement is rare in brucellosis. There is no presentation with pleural and pericardial effusion in childhood brusellosis. In endemic countries Brucellosis must thought as an unknown etiology of pericardial and pleural effusion.